Neprištevnost in procesna nesposobnost v dialogu med sodiščem in izvedencem psihiatrom - Kratovac, Alja (visokošolska dela, 2021)
The thesis focuses on the question of whether it is possible, and when it is possible, to use the institute of insanity in order to absolve the offender from guilt due to the doctrinal reason of the non-existence of a willing act. Furthermore, it explores why, in practice, the institute of insanity is used when a decision of acquittal should be issued, as it was established that willingness to act did not exist. Who, today, is the person for whom the assumption of sanity exists and how are offenders who do not understand their actions, and for various reasons cannot control them, treated in terms of law and of criminal policy. From the doctrinal point of view, they can be treated on a narrow bipolar axis: mentally ill by using the institute of insanity, mentally healthy by using the rules regarding willingness to act and guilt.
Keywords: biološko-psihološka metoda; Disertacije; Neprištevnost; Pravdni postopek; procesna nesposobnost; uporaba instituta neprištevnosti v praksi